THE ROLE OF DERIVATION IN ENGLISH WORD FORMATION (Ustozlar uchun, 2026)
Word formation is a central and dynamic aspect of linguistic creativity. Among the key processes that expand the English vocabulary, derivation holds a fundamental role, shaping both the structure and meaning of words. As language users create and adapt to new realities, derivational processes enable the flexibility that keeps English lively and adaptive. This article delves into the nature, mechanisms, and significance of derivation in English word formation, tracing its impact throughout both historical and modern contexts.